(3fcJ GdCeGdj Ydi YbO GddBdjs - (3CHhMjGf eMeO Hf jhSa Hf Ydj GdCfOdSjs; (3CHh MjGf GdfMhj , eMeO Hf jhSa Hf Ydj Hf jhSa Hf MjGf GdfaRj GdZQfGWj, GKjQ GdOjf,J (B745 (3g` s ((3CMeO Hf YHOGdcQje GdEHjGQj s)
(3ChdgG (B:s
(3gPg fcJ cJHJgG Ydi Lgg GdTQM GdeNJU dbUjOJj aj GdbQGAGJ hSejJgG fcJ GdCeGdi Ydi YbO GddGdj s
(3BNQgG (B:s
(3HbUg dehSi gj bhdg hjchf dceG GdcHQjGA aj GdCQV hbhdg Shi NWHI ZQB GdNWHI JSYg YTQ HjJkoG aUGQ LejY GdbUjO Cda HjJ hCQHYg hCQHYjf HjJkG s
(3aj UaMI GdYfhGf ELGRI HNW EHQGgje Hf Ydi GdbQTj GdebQj GdbdbTfOj SfI (B912 (3g` dYHO GdbGOQ Hf MSf Hf MSjf Gdajhejs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs